(3UdI GdSeW hSeI GdeQW aj TQM SeW GdfOi aj GdaNQ GdeMeOis - (3eMeO Hf Ydj Hf eMeO GdJhRQi GdeYQha HGHf GdTHGWs; (3eMeO Hf jMji Hf Ydj GdTbQGWjSj,J (B466 (3g` s ((3eOjfI JhQR s)
(3ChdgG (B:s
(3MdJ ZfGFge ai SGjQ GdMdd LQhGHgf Pjhd GdYUH hGdMdd GdCdaGX MdJ Pi fRdJ hUGQ jbGd MddJ HGdecGf HGdaJM JMd HGdVeI MdkG hMdhdkG s
(3BNQgG (B:s
(3aCHOd ef GdJGA MQa jfGSH GdUGO ai GdEWHGb hGdESJYdGA hjfGSH GdJGA ai GdeNQL hgh GdWGA s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs